Neuroprotective Effect of Oxysophocarpine by Modulation of MAPK Pathway in Rat Hippocampal Neurons Subject to Oxygen–Glucose Deprivation and Reperfusion - Zhao, Peng; Chang, Ren-Yuan; Liu, Ning; Wang, Jing; Zhou, Ru; Qi, Xue; Liu, Yue; Ma, Lin; Niu, Yang; Sun, Tao; Li, Yu-Xiang; He, Yan-Ping; et al. (Cellular and molecular neurobiology, 2018)
Oxysophocarpine (OSC), an alkaloid isolated from Sophora flavescens Ait, has been traditionally used as a medicinal agent based on the observed pharmacological effects. In this study, the direct effect of OSC against neuronal injuries induced by oxygen and glucose deprivation (OGD) in neonatal rat primary-cultured hippocampal neurons and its mechanisms were investigated. Cultured hippocampal neurons, which were exposed to OGD for 2 h followed by a 24 h reoxygenation, were used as an in vitro model of ischemia and reperfusion. 2-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and lactate dehydrogenase (LDH) assay were used to confirm neural damage and to further evaluate the protective effects of OSC. The concentration of intracellular-free calcium [Ca 2+ ] i and mitochondrial membrane potential (MMP) were measured to determine the intracellular mechanisms and to further estimate the degree of neuronal damage. Changes in expression of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, p-ERK1/2, p-JNK1/2, and p-p38 MAPK were also observed in the in vitro model. It was shown that OSC (0.8, 2, or 5 µmol/L) significantly attenuated the increased absorbance of MTT, and the release of LDH manifests the neuronal damage by the OGD/R. Meanwhile, the pretreatment of the neurons during the reoxygenation period with OSC significantly increased MMP; it also inhibited [Ca 2+ ] i the elevation in a dose-dependent manner. Furthermore, the pretreatment with OSC (0.8, 2, or 5 µmol/L) significantly down-regulated expressions of IL-1β, TNF-α, p-ERK1/2, p-JNK1/2, and p-p38 MAPK in neonatal rat primary-cultured hippocampal neurons induced by OGD/R injury. In conclusion, OSC displays a protective effect on OGD-injured hippocampal neurons by attenuating expression of inflammatory factors via down-regulated the MAPK signaling pathway.